The Effectiveness of Static Figure, Dynamic Picture Ball-and-Stick, and Simple Molecules Model From Pin in the Shape Learning and Polarity of Molecules - Muhammad Ardiansyah (Universitas Negeri Malang, 2014)
Keefektifan Gambar Statis, Gambar Dinamis Ball-and-Stick, dan Model Molekul Sederhana Dibuat dari Jarum Pentul  pada Pembelajaran Bentuk dan Kepolaran Molekul Abstract: The aim of this study was to compare the effectiveness of static images, dynamic images of ball-and-stick, and models of simple molecules made of a pin in terms of cognitive learning outcomes of students in learning the shape and polarity of molecules. The research data is a cognitive achievement scores of students were collected using a multiple-choice test consisting of 35 items with content validity test is 87.6%, and the reliability coefficient, calculated by the formula KR-21, 0.90. Data were analyzed using t-test statistic. The results showed that the scores of cognitive learning outcomes of students who gained from learning the shape and polarity of the molecules by using simple molecular models made of a pin higher than using a dynamic picture of ball-and-stick, and score students' cognitive learning results obtained from the study of form and polar molecules by using a dynamic picture of ball-and-stick higher than using a static image. Based on these results it can be concluded that the model of simple molecules made of a pin is the most effective model of learning the shape and polarity of molecules. Key Words: static images, dynamic images, a molecular model of a pin, molecular shape, molecular polarity Abstrak: Tujuan penelitian ini adalah untuk membandingkan keefektifan gambar statis, gambar di-namis ball-and-stick, dan model molekul sederhana dibuat dari jarum pentul ditinjau dari hasil belajar kognitif siswa pada pembelajaran bentuk dan kepolaran molekul. Data penelitian adalah skor hasil belajar kognitif siswa yang dikumpulkan dengan menggunakan tes pilihan ganda yang terdiri dari 35 item dengan validitas isi tes sebesar 87,6%, dan koefisien reliabilitas, dihitung dengan rumus KR-21, sebesar 0,90. Data penelitian dianalisis menggunakan statistik uji t. Hasil penelitian menunjukkan bahwa skor hasil belajar kognitif siswa yang diperoleh dari pembelajaran bentuk dan kepolaran molekul dengan menggunakan model molekul sederhana dibuat dari jarum pentul lebih tinggi daripada menggunakan gambar dinamis ball-and-stick, dan skor hasil belajar kognitif siswa yang diperoleh dari pembelajaran bentuk dan kepolaran molekul dengan menggunakan gambar dinamis ball-and-stick lebih tinggi daripada menggunakan gambar statis. Berdasarkan hasil tersebut maka dapat disimpulkan bahwa model molekul sederhana dibuat dari jarum pentul merupakan model yang paling efektif pada pembelajaran bentuk dan kepolaran molekul. Kata kunci: gambar statis, gambar dinamis, model molekul jarum pentul, bentuk molekul, kepolaran molekul